2014
DOI: 10.1016/j.ydbio.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

TAF4b promotes mouse primordial follicle assembly and oocyte survival

Abstract: Primary ovarian insufficiency (POI) affects 1% of women under the age of 40 and is associated with premature ovarian follicle depletion. TAF4b deficiency in adult female mouse models results in hallmarks of POI including stereotyped gonadotropin alterations indicative of early menopause, poor oocyte quality, and infertility. However, the precise developmental mechanisms underlying these adult deficits remain unknown. Here we show that TAF4b is required for the initial establishment of the primordial follicle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…Taf4b-deficient female mice are viable but infertile and suffer from many hallmarks of premature ovarian failure, including follicle depletion, persistent estrous and high serum levels of the gonadotropin follicle stimulating hormone (FSH) (Falender et al, 2005;Freiman et al, 2001;Lovasco et al, 2010;Voronina et al, 2007). Recent work has demonstrated that Taf4b-deficient ovaries experience dramatic germ cell loss by apoptosis immediately after birth, the time at which the ovarian reserve is established (Grive et al, 2014). Furthermore, Taf4b-deficient females experience delayed cyst breakdown and defective primordial follicle assembly.…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Taf4b-deficient female mice are viable but infertile and suffer from many hallmarks of premature ovarian failure, including follicle depletion, persistent estrous and high serum levels of the gonadotropin follicle stimulating hormone (FSH) (Falender et al, 2005;Freiman et al, 2001;Lovasco et al, 2010;Voronina et al, 2007). Recent work has demonstrated that Taf4b-deficient ovaries experience dramatic germ cell loss by apoptosis immediately after birth, the time at which the ovarian reserve is established (Grive et al, 2014). Furthermore, Taf4b-deficient females experience delayed cyst breakdown and defective primordial follicle assembly.…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
“…Impaired cyst breakdown; loss of primordial follicles (Lechowska et al, 2011;Rajkovic et al, 2004;Suzumori et al, 2002) TBP-associated Factor 4b (Taf4b) Impaired cyst breakdown; loss of primordial follicles (Falender et al, 2005;Freiman et al, 2001;Grive et al, 2014;Lovasco et al, 2010;Voronina et al, 2007) …”
Section: Signaling During Primordial Follicle Formationmentioning
confidence: 99%
“…Whole ovaries were incubated with TRA98 antibody (BBridge) diluted 1:100 to label germ cells [17,18] and with cleaved PARP (product no. E51; Abcam) diluted 1:100 to label cells undergoing apoptosis overnight and then with goat anti-rat secondary Alexa 488 and goat anti-rabbit Alexa 568, respectively.…”
Section: Tra98 and Cleaved Parp Immunohistochemistrymentioning
confidence: 99%
“…23,25,[28][29][30][31] Several tissue-specific variants of TAFs have been discovered: TAF4 variants are important for ovarian development and spermatogenesis in mice, while Drosophila and human TAF5 and TAF7 paralogs are implicated in male gametogenesis, thus providing the TFIID with unique functions in a tissue-specific transcription environment. [32][33][34][35][36][37] Following the binding of TFIID, TFIIA binds and stabilizes the association of TFIID with the TATA-box. The formation of the TFIID-TFIIA-DNA complex is followed by the sequential binding of TFIIB, RNAP II/TFIIF, TFIIE and TFIIH, resulting in the assembly of the PIC.…”
Section: Introductionmentioning
confidence: 99%